Perspektif Islam dalam Kepemimpinan: Sebuah Studi di Lembaga Pendidikan Islam - Farihin Farihin (Prodi Manajemen Pendidikan Islam Pascasarjana Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
This research examines leadership in an Islamic perspective. Where several studies show the dynamics of leadership with employee motivation and discipline which often affect performance within organizational groups. As a leader, you should have a management style and method to achieve your goals. As an institution that is in the Islamic education environment, this research examines how leaders position themselves from various religious dimensions such as perspective, management methods and employee credibility in an Islamic education environment that is thick with religious culture. This study uses a qualitative approach through observation, interviews and documentation. The results of this study indicate that Islamic values in Al-Quran and Al-Hadisth as well as the guidance of the Prophet Muhammad SAW become guidelines in managerial leadership that are able to create an Islamic culture that is thick with exemplary values, namely Shidiq, Tabligh, Amanah, Fathonah. The results of this research are expected to contribute to theoretical leadership in Islamic Education Institutions in the future.